PENGARUH MARKETING 4.0 TERHADAP CUSTOMER SATISFACTION DAN REPURCHASE INTENTION (Studi Pada Pengguna Smartphone di Semarang) - Andy Adrian Prasetya; I Made Bayu Dirgantara; Ardiaz Ajie Aryandika (Diponegoro Journal of Management, 2023)
ABSTRACT This study evaluates the role of the Marketing 4.0 component in maximizing customer satisfaction and influencing repurchase intentions with these four components, namely: Brand Identity, Brand Image, Brand Integrity, and Brand Interaction to support a company's marketing. The population in this study were smartphone users in the city of Semarang who knew and had bought a smartphone and knew of the attributes of marketing 4.0. The number of samples used is 100 respondents. The data obtained from the questionnaire data were then analyzed using structural equation modeling or SEM. The results of this study indicate that the marketing dimension 4.0 on smartphones has a positive effect on customer satisfaction. Furthermore, customer satisfaction has a positive effect on repurchase intentions and customer satisfaction is able to provide a significant influence in mediating marketing 4.0 on repurchase intentions